RECOLONIZACIÓN Y CIENCIAS SOCIALES - Lopez y Rivas , Gilberto (2024)
In this paper, it expose che challenges to social sciences in the beginning of the third millennium, from reaching changes wrought by neoliberal transnationalization. These changes are characterized as a recolonization and integral occupation of our countries. Many of che processes, actors and social subjects that have been of interest in the social sciences: inequality and exclusion of indigenous peoples and their autonomy, contained in che nacional ethnic question, the dynamics and socio-cultural identities, the relationship between local and the global, the deepening violence, racism and xenophobia aga inst migrants, the agrarian • peasant question • among others • have been marked by the effects of this neocolonial globalization, that has also meant a significant change in the nature of the nation-state and a real geopolitical transformation of the world.